2018
DOI: 10.1139/cjpp-2017-0394
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pharmacological inductors of HSP70 enhance the antioxidative defense mechanisms of the liver and pancreas in diabetic rats

Abstract: Heat preconditioning (HP) is a powerful adaptive and protective phenomenon and the heat stress proteins (HSPs) it produces are an important determinant for the development of diabetic complications. Aspirin has been reported to modulate heat shock response in different organisms through increased induction of HSPs and is also known to exert antioxidative and radical scavenging effects in diabetes. We estimated the effect of physiological (heat stress: 45 min at 41 ± 0.5 °C) and pharmacological (aspirin treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…Similarly, the depleted expression of HO-1, an antioxidant responsive protein, was also increased by aspirin treatment, in both the liver and kidney of GK rats. These results are consistent with previous studies showing enhanced antioxidative defense mechanisms in diabetic rats treated with aspirin [44][45][46]. In addition, our studies on selected CYP 450s, CYP 2E1 and CYP 3A4 have demonstrated that these enzyme activities were markedly increased in diabetes, confirming our earlier reports on the changes in CYP 450s [8,10,11].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the depleted expression of HO-1, an antioxidant responsive protein, was also increased by aspirin treatment, in both the liver and kidney of GK rats. These results are consistent with previous studies showing enhanced antioxidative defense mechanisms in diabetic rats treated with aspirin [44][45][46]. In addition, our studies on selected CYP 450s, CYP 2E1 and CYP 3A4 have demonstrated that these enzyme activities were markedly increased in diabetes, confirming our earlier reports on the changes in CYP 450s [8,10,11].…”
Section: Discussionsupporting
confidence: 93%
“…In terms of the mechanisms by which HSP70 inactivation contributes to enhanced cell killing, it is logical to propose sustained checkpoint signaling due to impaired DNA repair, but additional mechanisms, including ROS or stress MAPK signaling (e.g., p38 and ERK), may directly contribute to stabilization and stronger phosphorylation of p53 and induction of its target genes (112,113). This conclusion is further supported by our findings and previous reports showing that HSP70 inhibits ROS production (114,115), and by binding and modulating the endonuclease activity of HAPE1 (59), it may improve DNA repair activity. Other mechanisms, such as enhanced ROS production in hsp70 Ϫ/Ϫ cells that is positively regulated by both DDR-induced p53 target gene expression (PIG) and mitochondrial impairment, may augment the selective killing of DNA-damaged cells through p53-dependent or -independent mechanisms of action (116).…”
Section: Discussionsupporting
confidence: 87%
“…First of all, we found about 2.9-fold increase of HSP70 protein level in the heart 24 h hours after the HS and additional production of HSP70 for about 6.8 fold when ASA was given as a pretreatment to acute HS. Our assumption is this is a direct consequence of the elevation of the rectal temperature for about 3.7 °C after the given heat stress (45 min, 41±0.5 °C) (24). In addition to this, we have already observed that more intensive rise of the rectal temperature, which was about 4.5 °C higher than in control rats when ASA treatment was given before HS (24).…”
Section: Discussionmentioning
confidence: 60%
“…As a follow up of our previous work (24,25), where metabolic changes in pancreas and liver were investigated, we continued our work with a heart as a tissue, and effect of heat stress with or without ASA pretreatment in the control and diabetic rats, since the heart has specific carbohydrate metabolism.…”
Section: Discussionmentioning
confidence: 99%